2017
DOI: 10.22231/asyd.v14i3.641
|View full text |Cite
|
Sign up to set email alerts
|

Espacios productivos y roles domésticos en granjas de leche en pequeña escala en México.

Abstract: ResumenLa participación de las mujeres en actividades agropecuarias en México ha sido invisibilizada puesto que son los hombres quienes toman las decisiones y ostentan el control sobre los medios productivos. Por el contrario, en el ámbito doméstico, la participación masculina no parece tener una contribución significativa ni visible, ya que son las mujeres las responsables de estos espacios. Este proceso de invisibilización de ambos géneros condujo este artículo hacia la exploración de los espacios y las rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Addressing water scarcity emerges as a critical factor for sustainable dairy farming, suggesting strategies like raising replacements and growing feed inputs in less arid regions . The impact of urban growth on rural areas and migration trends among younger generations underscores the need for comprehensive strategies that involve the small and medium-scale dairy sector in shaping the future (Bullock and Crane, 2021;Moreno-Ramos, 2021;Ruiz-Torres et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Addressing water scarcity emerges as a critical factor for sustainable dairy farming, suggesting strategies like raising replacements and growing feed inputs in less arid regions . The impact of urban growth on rural areas and migration trends among younger generations underscores the need for comprehensive strategies that involve the small and medium-scale dairy sector in shaping the future (Bullock and Crane, 2021;Moreno-Ramos, 2021;Ruiz-Torres et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the informants' narrative, we can infer that this backyard pig production model has been developed and reproduced for at least 150 years, which implies that between six and eight generations have made a cultural investment in its social reproduction (Martínez-Castañeda and Perea-Peña, 2012). The fact that all members of the family, be it nuclear or extended, are involved in the tasks that the activity imposes, ensures its social reproduction (Ruiz-Torres et al, 2017). The producers reported that they sell both to intermediate consumers and to final consumers.…”
Section: Resultsmentioning
confidence: 99%
“…Also, farmers rely on dairy farming as the main source of income (Juárez-Morales et al, 2017). In the area, four physical spaces with clearly defined gender roles interact: The stable and productive lands are associated with masculine roles, whereas the house and milpa (cultivated field) are associated with feminine roles (Ruiz-Torres et al, 2017). -Sánchez et al (2014) reported a total of 900 small-scale dairy production farms in the study area.…”
Section: Study Areamentioning
confidence: 99%
“…As mentioned, the backyard is one strategy for supplementing the basic food basket. Backyard may be characterized as an asset storage strategy or as a living pantry that provides vegetables, fruits, and animal protein such as meat and eggs (Ruiz-Torres et al, 2017). The animal diversity present in farms is related to families' perceptions of the utility of animals and the number of animals that families can feed.…”
Section: Martínezmentioning
confidence: 99%